Culture-based and Sanger sequencing approaches to uncover the diversity of leaf-fungal endophytes in neotropical gymnosperms - Omayra Meléndez; Rita Bethancourt; Ariadna Bethancourt; Lilisbeth Rodríguez–Castro; Jorge Mendieta; Armando A. Durant Archibold; Marta Vargas; Brian Sedio; Kristin Saltonstall; Juan Carlos Villarreal A. (Tecnociencia)
Endophytic fungi play a crucial role in the survival and adaptation of their host plants. In recent decades, unprecedented diversity of endophytic fungi has been reported in angiosperms, but knowledge about this diversity in tropical gymnosperms is lacking. Among gymnosperms, cycads (Cycadales) are important components of Neotropical forests with high levels of endemism in Central and South America. We used a combination of axenic culture and Sanger sequencing to isolate and identify leaf endophytes of two endemic cycads from humid forests of Panama, Zamia nana and Z. pseudoparasitica. The latter is the only known epiphytic gymnosperm. In Z. pseudoparasitica, 50 morphotypes were isolated from El Copé, 58 from Santa Fe, and 22 from Cerro Marta.  We sampled one wild population of Z. nana (El Valle de Antón), from which we recovered 74 morphotypes. We also sampled Z. nana from the International Garden of Cycads in Panama City. Sequencing of 69 cultures with the ITS rRNA locus identified several ascomycetes: Colletotrichum, Cercophora, Hypoxylon, Phyllosticta, Xylaria, and a basidiomycete: Tritirachium. This is one of the first studies to document the diversity of endophytic fungi in a Neotropical gymnosperm and provides a window into the endophytic fungi that inhabit the leaves of tropical plants.